2020
DOI: 10.1029/2019jd031087
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the Appearance of Optical Lightning Flashes Observed From Space According to Thunderstorm Organization and Structure

Abstract: Optical lightning observations from space reveal a wide range of flash structure. Lightning imagers such as the Geostationary Lightning Mapper and Lightning Imaging Sensor measure flash appearance by recording transient changes in cloud top illumination. The spatial and temporal optical energy distributions reported by these instruments depend on the physical structure of the flash and the distribution of hydrometeors within the thundercloud that scatter and absorb the optical emissions. This study explores ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 73 publications
(111 reference statements)
0
26
0
Order By: Relevance
“…While a peak at noon might appear to suggest solar contamination, analyzing the 52 flashes that contribute to this peak (11:00:00 -12:59:59) indicated that these flashes were primarily landbased (87%) and occurred in large MCSs like their nocturnal counterparts. Noontime megaflashes can even be noted in the multi-day MCS event analyzed in Peterson et al (2020c). These analyses demonstrate two important points about the top lightning megaflashes.…”
Section: Measuring Lightning Flash Extent and Duration With Glmmentioning
confidence: 71%
See 1 more Smart Citation
“…While a peak at noon might appear to suggest solar contamination, analyzing the 52 flashes that contribute to this peak (11:00:00 -12:59:59) indicated that these flashes were primarily landbased (87%) and occurred in large MCSs like their nocturnal counterparts. Noontime megaflashes can even be noted in the multi-day MCS event analyzed in Peterson et al (2020c). These analyses demonstrate two important points about the top lightning megaflashes.…”
Section: Measuring Lightning Flash Extent and Duration With Glmmentioning
confidence: 71%
“…Peterson et al (2020c) plots the group-level structure of GLM flashes at 17 UTC (12 CT), and a large flash can be seen extending behind the convective line in the stratiform region that developed over the previous day.Accepted for publication in Bulletin of the American Meteorological ociety. DOI S 10.1175/BAMS-D-20-0178.1.…”
mentioning
confidence: 99%
“…We previously reported cases of highly irregular radiance patterns where the shape of the optical pulse on the CCD imaging array followed the cloud boundaries (i.e., Figures 3 and 4 in Peterson, Deierling, et al, 2017), cases where the radiance pattern extended outward from the edge of the thunderstorm core giving an incorrect impression that these warm boundary clouds were producing lightning (Peterson, Rudlosky, et al, 2017), and cases where optical emissions were blocked from reaching orbit by certain cloud regions, resulting in “holes” in otherwise‐contiguous flash footprints (i.e., Figure 1 in Peterson & Liu, 2013). Unobscured lightning sources have also been proposed as the mechanism responsible for certain lightning “superbolts” (Turman, 1977) that primarily illuminate the edge of the storm (Peterson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The most energetic optical pulses recorded by LIS typically occurred in one of two scenarios: "anvil superbolts" where most of the illuminated pixels were located near cloud boundaries outside of the raining area of the storm, and "stratiform superbolts" that almost exclusively illuminated raining stratiform clouds. Peterson et al (2020b) also used continuous Geostationary Lightning Mapper (GLM: Goodman et al, 2013;Rudlosky et al, 2019) observations to examine how lightning characteristics changed over time within a single storm system. These analyses showed that early convection was favorable for large flashes that lacked apparent lateral motion.…”
Section: Superbolts As Normal Lightningmentioning
confidence: 99%